ERK5 Is Required for Tumor Growth and Maintenance Through Regulation of the Extracellular Matrix in Triple Negative Breast Cancer - Hoang, Van T.; Matossian, Margarite D.; Ucar, Deniz A.; Elliott, Steven; La, Jacqueline; Wright, Maryl K.; Burks, Hope E.; Perles, Aaron; Hossain, Fokhrul; King, Connor T.; Browning, Valentino E.; Bursavich, Jacob; et al. (Frontiers in Oncology, 2020)
Conventional mitogen-activated protein kinase (MAPK) family members regulate diverse cellular processes involved in tumor initiation and progression, yet the role of ERK5 in cancer biology is not fully understood. Triple-negative breast cancer (TNBC) presents a clinical challenge due to the aggressive nature of the disease and a lack of targeted therapies. ERK5 signaling contributes to drug resistance and metastatic progression through distinct mechanisms, including activation of epithelial-to-mesenchymal transition (EMT). More recently a role for ERK5 in regulation of the extracellular matrix (ECM) has been proposed, and here we investigated the necessity of ERK5 in TNBC tumor formation. Depletion of ERK5 expression using the CRISPR/Cas9 system in MDA-MB-231 and Hs-578T cells resulted in loss of mesenchymal features, as observed through gene expression profile and cell morphology, and suppressed TNBC cell migration. In vivo xenograft experiments revealed ERK5 knockout disrupted tumor growth kinetics, which was restored using high concentration MatrigelTM and ERK5-ko reduced expression of the angiogenesis marker CD31. These findings implicated a role for ERK5 in the extracellular matrix (ECM) and matrix integrity. RNA-sequencing analyses demonstrated downregulation of matrix-associated genes, integrins, and pro-angiogenic factors in ERK5-ko cells. Tissue decellularization combined with cryo-SEM and interrogation of biomechanical properties revealed that ERK5-ko resulted in loss of key ECM fiber alignment and mechanosensing capabilities in breast cancer xenografts compared to parental wild-type cells. In this study, we identified a novel role for ERK5 in tumor growth kinetics through modulation of the ECM and angiogenesis axis in breast cancer.